1992
DOI: 10.1136/bjo.76.5.292
|View full text |Cite
|
Sign up to set email alerts
|

Corneal diameter in premature infants.

Abstract: The size of the cornea is important in the diagnosis of primary infantile glaucoma. Reference values regarding eyes of premature infants are scarce. Such data are of special importance in areas such as the Middle East where infantile glaucoma is common and often evident already at birth. The authors have measured the horizontal corneal diameter of the eyes of 127 premature Saudi infants with a gestational age between 23 and 36 weeks and a birth weight ranging from 540 g to 4720 g. The corneal diameter ranged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…Fundus examinations reveal that the corneas of premature infants (less than 30 gestational weeks) are often blurred, while most infants of over 31 gestational weeks have sufficient corneal clarity. These findings suggest that corneal hydration in premature infants can play an important role in determining the central corneal thickness (13) . Recent studies have shown that corneal thickness in premature babies decreases towards the time of full-term (13,14) .…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Fundus examinations reveal that the corneas of premature infants (less than 30 gestational weeks) are often blurred, while most infants of over 31 gestational weeks have sufficient corneal clarity. These findings suggest that corneal hydration in premature infants can play an important role in determining the central corneal thickness (13) . Recent studies have shown that corneal thickness in premature babies decreases towards the time of full-term (13,14) .…”
Section: Discussionmentioning
confidence: 72%
“…These findings suggest that corneal hydration in premature infants can play an important role in determining the central corneal thickness (13) . Recent studies have shown that corneal thickness in premature babies decreases towards the time of full-term (13,14) . Kirwan et al found that babies born at 31 weeks have thick corneas and that a progressive and statistically significant decrease in thickness occurs towards full-term.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Recently, Denis et al (1998) also reported similar results. However, there have been some studies that reported slightly higher value in premature infants (Musarella and Morin, 1985;Al-Umran and Pandol®, 1992).…”
Section: Discussionmentioning
confidence: 94%
“…Increased CCT and peripheral corneal thickness in neonates is thought to be related to prolonged eye closure in utero and decreasing thickness after birth is due to better control of corneal hydration [8]. Uva Results are denoted as mean ± SD (minimum-maximum) Int Ophthalmol et al [4] compared the CCT and IOP values in both premature and term infants and they reported that the IOP measurements of premature infants were slightly greater than in term infants because of an increased CCT.…”
Section: Discussionmentioning
confidence: 98%